2014
DOI: 10.1002/ece3.1012
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric reproductive barriers and mosaic reproductive isolation: insights fromMisty lake–stream stickleback

Abstract: Ecological speciation seems to occur readily but is clearly not ubiquitous – and the relative contributions of different reproductive barriers remain unclear in most systems. We here investigate the potential importance of selection against migrants in lake/stream stickleback (Gasterosteus aculeatus) from the Misty Lake system, Canada. This system is of particular interest because one population contrast (Lake vs. Outlet stream) shows very low genetic and morphological divergence, whereas another population co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…Indeed, Atlantic mtDNA haplotypes of sea bass have not been observed to naturally introgress the Western Mediterranean Sea population so far, while the reverse was regularly observed (Coscia et al., 2012; Lemaire et al., 2005; Rondon, 2011). This may represent a case of asymmetric selection against migrants resulting in asymmetric reproductive isolation (Gagnaire, Normandeau, & Bernatchez, 2012; Räsänen & Hendry, 2014). Because of pleiotropy (see above), asymmetric selection could act on early survival and favor sex determination of the individuals ♂ WEM × ♀ NAT cross as males as suggested by Lemaire et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Atlantic mtDNA haplotypes of sea bass have not been observed to naturally introgress the Western Mediterranean Sea population so far, while the reverse was regularly observed (Coscia et al., 2012; Lemaire et al., 2005; Rondon, 2011). This may represent a case of asymmetric selection against migrants resulting in asymmetric reproductive isolation (Gagnaire, Normandeau, & Bernatchez, 2012; Räsänen & Hendry, 2014). Because of pleiotropy (see above), asymmetric selection could act on early survival and favor sex determination of the individuals ♂ WEM × ♀ NAT cross as males as suggested by Lemaire et al.…”
Section: Discussionmentioning
confidence: 99%
“…). However, a transplant experiment later indicated that selection against immigrants, together with various other factors, might be contributing to reproductive isolation in this system (Räsänen & Hendry ). Similarly, we cannot rule out that barriers, which we did not detect in our experiment, could contribute to reproductive isolation among lake and stream populations.…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocal transplant experiments provide so far the strongest evidence for divergent selection by demonstrating that ecotypes or incipient species suffer from reduced fitness in each other's environment (reviewed in Hereford, 2009). Such studies are commonly performed in plants (reviewed in Leimu & Fischer, 2008) and are becoming more and more common in insects and fish that inhabit temperate habitats of the northern hemisphere (e.g., Räsänen & Hendry, 2014;Soria-Carrasco et al, 2014;Gosden, Waller, & Svensson, 2015;Moser, Frey, & Berner, 2016;Soudi, Reinhold, & Engqvist, 2016;Kaufmann, Lenz, Kalbe, Milinski, & Eizaguirre, 2017). Very few such studies have, however, been conducted with animals that inhabit remote areas in the tropical climate (e.g., Thorpe, Reardon, & Malhotra, 2005;Schwartz, Weese, Bentzen, Kinnison, & Hendry, 2010;Bongaerts et al, 2011;Kenkel & Matz, 2016).…”
mentioning
confidence: 99%